Respuesta :

Answer:

OPTION - 3: -m²n³[tex]$ \sqrt{n} $[/tex]

Step-by-step explanation:

We know that [tex]$ \sqrt{ab} = \sqrt{a}\sqrt{{b} $[/tex]

Also, [tex]$ \sqrt{m^{2}} = m $[/tex]

Now we are to simplify: [tex]$ - \sqrt{m^4n^7} $[/tex]

[tex]$ \implies - \sqrt{m^4}\sqrt{n^7} $[/tex]

[tex]$ \implies - \sqrt{(m^2)^2}\sqrt{n^6.n} $[/tex]

[tex]$ \implies-  m^2 \sqrt{(n^3)^2.n} $[/tex]

[tex]$ \implies - m^2 n^3\sqrt{n}[/tex]

∴                       [tex]$ \sqrt{m^4n^7} =  -m^2n^3\sqrt{n} $[/tex]

ACCESS MORE